Chemical compounds targeting DNA methylation and hydroxymethylation - Belle, R; Kawamura, A; Arimondo, PB (Springer, 2019)
DNA methylation and its oxidised forms participate in the interpretation and regulation of the human genome. Many questions arise around the enzymes responsible for these chemical modifications on DNA, and their roles in transcriptional regulation. These epigenetic marks are very dynamic and specific in their location and context (tissues, diseases, etc.). We review the major enzymes involved in DNA methylation and oxidation, with a focus on the DNA methyltransferases and TET enzymes. The principal compounds that inhibit these enzymes are presented since they will help address these questions.